Effect of African leafy vegetables on the micronutrient status of mildly deficient farm-school children in South Africa: a randomized controlled study. Issue 5 (6th July 2015) - van der Hoeven, Marinka; Faber, Mieke; Osei, Jennifer; Kruger, Annamarie; Smuts, Cornelius M
Abstract: Objective: A randomized controlled trial was conducted to assess the effect of African leafy vegetable (ALV) consumption on Fe, Zn and vitamin A status in children. Design: Children were randomly allocated to receive either a 300 g cooked ALV dish and school meal starch ( n 86) or the normal school meal ( n 81) five times per week for three months. ALV in the dish consisted mainly of Amaranthus cruentus (at least 80 %) and the remainder of Cleome gynandra, Cucurbita maxima or Vigna unguiculata . Nutrient content and consumer acceptance of the ALV dish were also determined. Setting: North West Province, South Africa. Subjects: Grade R to grade 4 children (6–12 years old) of two farm schools. Results: The ALV dish contributed 11·6–15·8 mg Fe and 1·4–3·7 mg Zn. At baseline, prevalence of deficiencies in the intervention group was 16·0 %, 16·3 %, 7·0 % and 75·6 %, respectively, for anaemia (Hb<11·5 g/dl), Fe (serum ferritin<15 µg/l), vitamin A (serum retinol<20 μg/dl) and Zn (serum Zn<65 μg/dl); and in the control group 10·5 %, 18·5 %, 2·5 % and 75·3 %, respectively. No significant estimated intervention effect was found. Conclusions: This randomized controlled trial showed that ALV were unable to improve serum retinol, serum ferritin or Hb if there are only mild deficiencies present. Furthermore, despite the low Zn status in the study population, ALV consumption did not improve serum Zn concentrations either.